Compositional tuning of epoxide-polyetheramine "click" reaction toward cytocompatible, cationic hydrogel particles with antimicrobial and DNA binding activities. (1st October 2016) - Tang, Shuangcheng; Huang, Lu; Daniels-Mulholland, Robert J.; Dlugosz, Elizabeth; Morin, Emily A.; Lenaghan, Scott; He, Wei
Graphical abstract: Abstract: The "click" characteristics of nucleophilic opening of epoxide have recently been exploited for the development of a functional hydrogel particle system based on commercially available bisepoxide and triamine polyetheramine monomers. Key features of these particles include high cationic charges and responsiveness to temperature, pH, and oxidation. Despite these advantages, the cytocompatibility of these particles must be considered prior to use in biomedical applications. Here we demonstrate that, by introducing a diamine polyetheramine as a comonomer in the "click" reaction, and tuning its molar ratio with the triamine monomer, cationic nanoparticles with improved cytocompatibility can be prepared. The reduced cytotoxicity is primarily due to the hydrophilic backbone of the diamine comonomer, which has polyethylene glycol as a primary component. The resulting nanoparticles formed from the diamine comonomer exhibited a lower surface charge, while maintaining a comparable size. In addition, the responsiveness of the nanoparticles to temperature, pH, and oxidation was conserved, while achieving greater colloidal stability at basic pH. Results from this study further demonstrated that the nanoparticles were able to encapsulate Nile red, a model for hydrophobic drug molecules, were effective against the bacteria Staphylococcus aureus, and were capable of binding DNA through ionic complexation. Based on the results from this work, the use of diamine comonomers significantly reduces the cytotoxicity of similarly developed hydrogel nanoparticles, allowing for numerous biomedical applications, including nanocarriers for therapeutic agents with poor water solubility, treatment of bacterial infection, and non-viral vectors for gene therapy. Statement of Significance: In recent years significant attention has been placed on the development of nanocarriers for numerous biomedical applications. Of particular interest are cationic polymers, which contain high positive surface charges that allow binding of numerous therapeutic agents. Unfortunately, the advantages of cationic polymers for binding, are often negated by the tendency of these polymers to be cytotoxic. Previous studies have developed highly responsive cationic hydrogel nanoparticles, which meet several of the criteria for biomedical applications, but were acutely cytotoxic. In this work, cationic hydrogel nanoparticles, with significantly improved cytocompatibility, were synthesized using simple, green epoxy chemistry. In addition, the ability of these nanoparticles to maintain a small size (<500 nm), bind DNA, encapsulate hydrophobic drugs, and kill bacteria was maintained.